Glass article comprising n-doped graphene
Patent Information
- Application Number
- CN202280066319.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-03
- Filing Date
- 2022-07-29
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-07-29
Smart Images

Figure CN118103207B_ABST
Abstract
Description
[0001] Cross-reference to related applications
[0002] This application claims priority to U.S. Provisional Application No. 63 / 228825, filed August 3, 2021, pursuant to 35 USC §119, the contents of which are important herein and are incorporated herein by reference in their entirety. Technical Field
[0003] This disclosure relates to glass articles comprising n-doped graphene on at least one surface and methods for preparing the same. Background Technology
[0004] In the electronics field, pristine graphene lacks a bandgap, posing a challenge to field-effect transistor (FET) devices. This is due to the low ratio (e.g., below 100) between on-state and off-state currents (ION / IOFF); for example, the high performance of devices at low leakage power; comparing the 100 ratio of graphene-based FETs to approximately 10 of silicon's. 4 -10 7 The ratios are compared. In optics, it is known that graphene does not support any significant plasmon resonances near its neutral point (e.g., with almost no natural doping). However, graphene can support significant plasmon resonances by altering the doping (Fermi level) using an electrostatic field, which is limited by the dielectric breakdown of the layer to which the field is applied.
[0005] Graphene can be grown on metal films such as copper or nickel. After growth, it is transferred to a selected substrate, such as SiO2 for device fabrication. x / Si, high-performance fused silica (HPFS), or glass. When transferred to a substrate, graphene becomes doped due to its interaction with the surface. For example, on HPFS, graphene becomes p-doped, possessing 10 12 cm -2 Carrier density on the order of magnitude. This effect has been extensively documented in the literature in the case of graphene transfer to glass, where the process, along with the PMMA residue left after wet transfer methods, induces p-doping of the graphene because the glass possesses a potentially negative charge due to the hydroxyl groups on its surface. Therefore, doping following transfer to a properly treated surface is a means of opening the band gap and tuning the Fermi level. This is, for example, the case of ammonia and aluminum diffusion on oxide surfaces, which induces positive charges on the oxide layer (NSiO). + ) and negative charge (AlSiO) -Van der Pauw measurements show that, by manipulating surface charge, the charge neutrality, or Dirac voltage, in graphene can be increased from approximately -60 V (n = -8.62 × 10⁻⁶) on standard SiO₂. 12 cm –2 The voltage becomes approximately 13 V (n = 2.17 × 10⁻⁶) on the negatively doped SiO₂ layer. 12 cm –2 ). Summary of the Invention
[0006] As described herein, by placing graphene (e.g., pristine graphene) on the surface of ion-exchange glass, unexpectedly high carrier densities (e.g., approximately 10⁻⁶) have been developed. 13 cm -2 (or even higher) n-doped graphene. Such a high level of n-doping in graphene, resulting solely from interaction with the underlying substrate, has never been observed before.
[0007] Impurities may be introduced during glass synthesis, such as those introduced as a result of changes in the properties of the glass. For example, modifiers may be introduced into the glass during its synthesis, with Na and Ca atoms being typical additions (e.g., from Na₂O and CaO, respectively).
[0008] The absence of modifiers in quartz and fused silica results in strong covalent bonds between each silicon atom and four oxygen atoms, providing an extremely stable structure. Conversely, modifiers (such as Na in soda-lime glass) are essential. + The presence of Na results in weak ionic bonds, which allows ions to migrate at temperatures far below the glass transition temperature. The introduction of Na during glass synthesis promotes the breaking of some Si-O-Si bridges, leaving unbridged oxygen atoms in the glass network. These oxygen atoms will then bind with sodium cations (Na₂O₃). + The corresponding anion (O) - ), which is incorporated into these positions.
[0009] In the case of ion-exchange glasses, large ions can be introduced into the glass surface using ion exchange technology. In this process, the glass is placed in a hot bath of molten salt, for example, at about 400°C, at which temperature Na ions have sufficient mobility to leave the glass and exchange with K ions from the salt bath. This results in a surface layer with high compressive stress in the ion-exchange glass, thus providing its strength.
[0010] As described herein, it has been found that ion-exchange glasses naturally alter graphene doping without additional post-processing (e.g., thermal polarization under an applied potential). Thin-film resistance and Hall measurements performed at room temperature demonstrate that the high doping level of graphene placed in direct contact with the ion-exchange glass results in an unexpectedly high carrier density (e.g., approximately 10⁻⁶). 13 cm -2 (or on an even larger scale). It was found that the negative values obtained with ion-exchanged glass were several orders of magnitude larger than the positive values on union-exchanged natural silica or glass. Attached Figure Description
[0011] Referring to the following figures will provide a better understanding of these and other features, aspects, and advantages of this technology:
[0012] Figure 1-6 These are cross-sectional views of several examples of glass products ranging from 100 to 500.
[0013] Figure 7 This is a perspective view of an electronic device 120 including the glass articles described herein and an example of a method of manufacturing thereof.
[0014] Figure 8 This is a top view of the photolithographic pattern of the samples, showing two devices (device 1 and device 2) fabricated for each ion-exchange glass layer. A total of eight samples exist, each with 16 negatively doped graphene layers.
[0015] Figure 9 This is a graph of carrier density as a function of the ion-exchange thickness on the ion-exchange glass layer. The graph shows the evolution of graphene doping in eight samples as the ion-exchange thickness of the ion-exchange glass layer increases from 1 μm to 43 μm (corresponding to the top surface of the ion-exchange glass layer; the bottom surface of the ion-exchange glass layer has an equal ion-exchange thickness). The Dirac point at 0 (yellow area) separates the p-doped region (top green) from the n-doped region (bottom red).
[0016] It should be understood that the accompanying drawings are not necessarily drawn to scale, and the objects in the drawings are not necessarily drawn relative to each other. The drawings are intended to provide a clearer and more understandable description of the various embodiments of the devices, systems, and methods disclosed herein. The same reference numerals are used as much as possible throughout the drawings to refer to the same or similar parts. Furthermore, it should be understood that the drawings are not intended to limit the scope of this teaching in any way. Detailed Implementation
[0017] Unless otherwise stated, this disclosure is not limited to the specific compositions, articles, apparatus, and methods described herein. It should also be understood that the terminology used herein is for descriptive purposes only and is not intended to be limiting.
[0018] refer to Figure 1 This disclosure relates to a glass article 100, comprising: an ion-exchange glass layer 102 including a first main surface 104 of the ion-exchange glass layer and a second main surface 106 of the ion-exchange glass layer opposite to the first main surface; and at least one negatively doped graphene layer 108 having a first main surface 110 of the negatively doped graphene layer and a second main surface 112 of the negatively doped graphene layer opposite to the first main surface; the first main surface 110 of the negatively doped graphene layer is positioned opposite at least a portion of at least one of the first main surface 104 and the second main surface 106 of the ion-exchange glass layer 102, and the negatively doped graphene layer has at least about 10 13 cm -2 At least about 10 14 cm -2 or at least 10 15 cm -2 The carrier density. For example, a negatively doped graphene layer 108 can have a carrier density of approximately 10. 13 cm -2 To about 10 15 cm -2 Approximately 10 13 cm -2 To about 10 14 cm -2 Approximately 10 12 cm -2 To about 10 13 cm -2 Or about 10 13 cm -2 To about 10 14 cm -2 The carrier density.
[0019] Figure 2 One example is that the glass article 200 includes two negatively doped graphene layers, one positioned opposite at least a portion of the first main surface 104 of the ion-exchange glass layer 102, and the second negatively doped graphene layer 108A positioned opposite at least a portion of the second main surface 106 of the ion-exchange glass layer 102.
[0020] Figure 3 This relates to an example of a glass article 300, which includes: an ion-exchange glass layer 102; and a negatively doped graphene layer 108, wherein the negatively doped graphene layer 108 covers less than the entire first main surface 104 of the ion-exchange glass layer 102.
[0021] Figure 4One example is that the glass article 400 includes two negatively doped graphene layers, one positioned opposite at least a portion of a first main surface 104 of the ion-exchange glass layer 102, and the second negatively doped graphene layer 108A positioned opposite at least a portion of a second main surface 106 of the ion-exchange glass layer 102.
[0022] Figure 5 One example is that the glass article 500 includes a plurality (e.g., two) negatively doped graphene layers 108 and 108A, each negatively doped graphene layer being positioned on at least a portion of the first main surface 104 of the ion-exchange glass layer 102.
[0023] and Figure 1 The same applies to the instances in the example. Figure 2-5 The negatively doped graphene layer described in [the text] has at least about 10 [units / layers]. 13 cm -2 At least about 10 14 cm -2 or at least 10 15 cm -2 The carrier density. For example, a negatively doped graphene layer 108 can have a carrier density of approximately 10. 13 cm -2 To about 10 15 cm -2 Approximately 10 13 cm -2 To about 10 14 cm -2 Approximately 10 12 cm -2 To about 10 13 cm -2 Or about 10 13 cm -2 To about 10 14 cm -2 The carrier density. And in the presence of multiple negatively doped graphene layers (e.g., two, three, four or more; for example, Figure 2 , 4 In the cases of 108 and 108A in 5, each negatively doped graphene layer can have the same or different carrier densities.
[0024] The negatively doped graphene layers described herein may possess other suitable electrical properties, including a sheet resistance of about 200 Ω / sq to about 500 Ω / sq (e.g., about 200 Ω / sq to about 300 Ω / sq; about 250 Ω / sq to about 400 Ω / sq; about 300 Ω / sq to about 400 Ω / sq; about 400 Ω / sq to about 500 Ω / sq; about 250 Ω / sq to about 350 Ω / sq; or about 200 Ω / sq to about 250 Ω / sq); about 80 cm2 / V·s to approximately 800 cm 2 / V·s (e.g., approximately 80 cm) 2 / V·s to approximately 500cm 2 / V·s; approximately 200 cm 2 / V·s to approximately 500 cm 2 / V·s;150 cm 2 / V·s to approximately 250 cm 2 / V·s;200 cm 2 / V·s to approximately 400 cm 2 / V·s;150 cm 2 / V·s to approximately 250 cm 2 / V·s; or approximately 500 cm 2 / V·s to approximately 800 cm 2 Electron mobility of approximately 200 Ω / sq to approximately 500 Ω / sq (e.g., approximately 200 Ω / sq to approximately 300 Ω / sq; approximately 250 Ω / sq to approximately 400 Ω / sq; approximately 300 Ω / sq to approximately 400 Ω / sq; approximately 400 Ω / sq to approximately 500 Ω / sq; approximately 250 Ω / sq to approximately 350 Ω / sq; or approximately 200 Ω / sq to approximately 250 Ω / sq) and a sheet resistance of approximately 80 cm⁻¹ 2 / V·s to approximately 800 cm 2 / V·s (e.g., approximately 80 cm) 2 / V·s to approximately 500 cm 2 / V·s; approximately 200 cm 2 / V·s to approximately 500 cm 2 / V·s;150 cm 2 / V·s to approximately 250 cm 2 / V·s;200 cm 2 / V·s to approximately 400 cm 2 / V·s;150 cm 2 / V·s to approximately 250cm 2 / V·s; or approximately 500 cm 2 / V·s to approximately 800 cm 2 Both have electron mobility ( / V·s).
[0025] Figure 1-6The examples provided herein are examples of glass articles in which at least a portion of a first main surface of a negatively doped graphene layer is in direct contact with at least one of a first main surface of an ion-exchange glass layer and a second main surface of an ion-exchange glass layer. However, examples in which an intermediate layer (or multiple intermediate layers; not shown) exists between at least a portion of the first main surface of the negatively doped graphene layer and at least a portion of at least one of the first and second main surfaces of the ion-exchange glass layer are conceivable. Such intermediate layers can be used to provide additional features to the glass articles described herein (e.g., reflection resistance or antireflective properties, glare resistance or antireflective properties, color, opacity, and / or similar features) and can cover a portion or the entire ion-exchange glass layer (e.g., both the first and second main surfaces of the ion-exchange glass layer). Examples of intermediate layers include a coating of SiO2 nanoparticles bonded to at least a portion of the first and second main surfaces of the ion-exchange glass layer to provide antireflective properties (for example, finished glass articles). Alternatively, the intermediate layer may comprise a multilayer antireflective coating formed of alternating polycrystalline TiO2 and SiO2 layers. Alternatively, the intermediate layer may comprise a composition containing dye or pigment materials to provide color.
[0026] Typically, when an intermediate layer is present, it can be independently manufactured using any variation of chemical vapor deposition (CVD) (e.g., plasma-enhanced CVD, aerosol-assisted CVD, metal-organic CVD, etc.), any variation of physical vapor deposition (PVD) (e.g., ion-assisted PVD, pulsed laser deposition, cathodic arc deposition, sputtering, etc.), spraying, spin coating, dip coating, inkjet printing, sol-gel processing, etc. Such methods are known to those skilled in the art to which this disclosure pertains.
[0027] Any negatively doped graphene layer described herein can have any suitable thickness. For example, the negatively doped graphene layer described herein can have a thickness of about 1 nm or less. In some cases, the negatively doped graphene layer described herein has a thickness of about 0.1 nm to about 1 nm (e.g., about 0.1 nm to about 0.5 nm; about 0.5 nm to about 1 nm; about 0.1 nm to about 0.9 nm; about 0.25 nm to about 0.75 nm; about 0.25 nm to about 0.5 nm; or about 0.6 nm to about 1 nm).
[0028] One or more negatively doped graphene layers described herein can be positioned on an ion-exchange glass layer by any suitable method known in the art, including graphene transfer via a wet etching process with or without post-annealing. The ion-exchange glass layer can be cleaned with any suitable solvent prior to graphene transfer.
[0029] The graphene used to prepare the negatively doped graphene layer described herein can be prepared by any method known in the art, for example, by growing on copper by chemical vapor deposition (CVD) and transferring to an ion-exchange glass layer by a polymethyl methacrylate (PMMA)-based transfer process, wherein an additional annealing step may be added to enhance sample cleanliness.
[0030] Although the negatively doped graphene layer described in this article is Figure 1-6 The graphene layer is shown as a single layer, but negatively doped graphene layers may comprise graphene stacks comprising two or more graphene layers substantially one positioned on top of another (e.g., two or three layers). In the stack, the total thickness of the layers can still be about 1 nm or less. In some cases, negatively doped graphene stacks may have a thickness of about 0.3 nm to about 1 nm (e.g., about 0.3 nm to about 0.5 nm, about 0.5 nm to about 1 nm; about 0.3 nm to about 0.9 nm; about 0.3 nm to about 0.75 nm; or about 0.6 nm to about 1 nm).
[0031] The ion-exchange glass layers described herein can be prepared using any suitable method, including ion exchange methods, which specifically involve immersing a glass or glass-ceramic material in a molten salt bath for a predetermined time period, where ions at or near the surface of the glass or glass-ceramic material exchange with larger metal ions from the salt bath. In one embodiment, the temperature of the molten salt bath is in the range of about 400°C to about 430°C, and the predetermined time period is about 4 hours to about 24 hours; however, the immersion temperature and duration can vary depending on the composition of the material and the desired strength properties. The incorporation of larger ions into the glass or glass-ceramic material strengthens the material by generating compressive stress at or near the material surface in one or more near-surface regions. Corresponding tensile stresses are induced in one or more central regions at a distance from the material surface to balance the compressive stresses. Glass or glass-ceramic materials using this strengthening process can be more specifically described as chemically strengthened or ion-exchange glass or glass-ceramic materials.
[0032] In one example, sodium ions in the strengthened glass or glass-ceramic material are replaced by potassium ions from a molten bath (e.g., a potassium nitrate bath), although other alkali metal ions with larger atomic radii (e.g., rubidium or cesium) can replace smaller alkali metal ions in the glass. According to a specific embodiment, smaller alkali metal ions in the glass or glass-ceramic can be replaced by Ag. + Ion substitution. Similarly, other alkali metal salts, such as, but not limited to, sulfates, phosphates, halides, etc., can be used in ion exchange methods.
[0033] While not wishing to be bound by any particular theory, it is believed that the negative doping of negatively doped graphene layers is induced by the ion-exchange glass layer. For example, the negative doping of negatively doped graphene layers is induced by positively charged ions present in the ion-exchange glass layer. These positively charged ions include positively charged alkali metal ions. Positively charged ions can include potassium ions (K ions). + ).
[0034] At temperatures below the relaxible level of the glass network, the replacement of smaller ions with larger ions creates an ion distribution across the surface of the reinforced material, resulting in a stress distribution. The larger volume of ions entering the reinforced material generates compressive stress (CS) on the surface and tension (central tension or CT) at the center. The following relationship exists between compressive stress and central tension:
[0035]
[0036] Where t is the total thickness of the strengthened glass or glass-ceramic material, and the depth of compression (DOL) of the layer (also referred to herein as the depth of the compressed layer) is the depth of ion exchange (e.g., the depth of ion exchange present on at least one surface of the ion-exchange glass layer described herein). The exchange depth can be described as the depth within the strengthened glass or glass-ceramic material (i.e., the distance from the surface of the glass material to the central region of the glass or glass-ceramic material) at which ion exchange facilitated by the ion exchange process occurs.
[0037] The reinforced glass or glass-ceramic material used as the ion-exchange glass layer described herein may have a surface compressive stress of about 300 MPa or greater, such as 400 MPa or greater, 450 MPa or greater, 500 MPa or greater, 550 MPa or greater, 600 MPa or greater, 650 MPa or greater, 700 MPa or greater, 750 MPa or greater, or 800 MPa or greater. The strengthened glass or glass-ceramic material may have a compression depth of about 15 μm or greater, 20 μm or greater (e.g., 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or greater; or 1 μm to 100 μm, e.g., 5 μm to 50 μm) and / or a center tension of about 10 MPa or greater, 20 MPa or greater, 30 MPa or greater, 40 MPa or greater (e.g., 42 MPa, 45 MPa or 50 MPa or greater) but less than 100 MPa (e.g., 95, 90, 85, 80, 75, 70, 65, 60, 55 MPa or less). The strengthened glass or glass-ceramic material used as the ion-exchange glass layer described herein may have one or more of the following: a surface compressive stress greater than about 200 MPa, a compression depth greater than about 15 μm, and a center tension greater than about 18 MPa.
[0038] Various glass compositions can be used in glass materials (e.g., glass materials for preparing the ion-exchange glass layers described herein), and include alkali metal aluminosilicate glass compositions or alkali metal aluminoborosilicate glass compositions, although other glass compositions are also contemplated. Such glass compositions may be characterized as ion-exchangeable. As used herein, “ion-exchangeable” means that the material comprising the composition can exchange cations located at or near the material surface with cations of the same valence, whether larger or smaller in size.
[0039] For example, a suitable glass composition includes SiO2, B2O3, and Na2O, wherein (SiO2 + B2O3) ≥ 66 mol.% and Na2O ≥ 9 mol.%. In one embodiment, the glass plate includes at least 6 wt.% alumina. In another embodiment, the glass plate includes one or more alkaline earth metal oxides, such that the content of the alkaline earth metal oxide is at least 5 wt.%. In some embodiments, a suitable glass composition further includes at least one of K2O, MgO, and CaO. In one specific embodiment, the glass may include 61-75 mol.% SiO2; 7-15 mol.% Al2O3; 0-12 mol.% B2O3; 9-21 mol.% Na2O; 0-4 mol.% K2O; 0-7 mol.% MgO; and 0-3 mol.% CaO.
[0040] Another exemplary glass composition suitable for forming a mixed glass laminate includes: 60-70 mol.% SiO2; 6-14 mol.% Al2O3; 0-15 mol.% B2O3; 0-15 mol.% Li2O; 0-20 mol.% Na2O; 0-10 mol.% K2O; 0-8 mol.% MgO; 0-10 mol.% CaO; 0-5 mol.% ZrO2; 0-1 mol.% SnO2; 0-1 mol.% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 12 mol.% ≤ (Li2O + Na2O + K2O) ≤ 20 mol.% and 0 mol.% ≤ (MgO + CaO) ≤ 10 mol.%.
[0041] Another exemplary glass composition comprises: 63.5-66.5 mol.% SiO2; 8-12 mol.% Al2O3; 0-3 mol.% B2O3; 0-5 mol.% Li2O; 8-18 mol.% Na2O; 0-5 mol.% K2O; 1-7 mol.% MgO; 0-2.5 mol.% CaO; 0-3 mol.% ZrO2; 0.05-0.25 mol.% SnO2; 0.05-0.5 mol.% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 14 mol.% ≤ (Li2O + Na2O + K2O) ≤ 18 mol.% and 2 mol.% ≤ (MgO + CaO) ≤ 7 mol.%.
[0042] Another example of a glass composition includes alkali metal aluminosilicate glass comprising, substantially comprising, or comprising the following: 61-75 mol.% SiO2; 7-15 mol.% Al2O3; 0-12 mol.% B2O3; 9-21 mol.% Na2O; 0-4 mol.% K2O; 0-7 mol.% MgO; and 0-3 mol.% CaO.
[0043] Another example of a glass composition includes an alkali metal aluminosilicate glass comprising alumina, at least one alkali metal, and, in some embodiments, greater than 50 mol.% SiO2, in other embodiments, at least 58 mol.% SiO2, and in still other embodiments, at least 60 mol.% SiO2, wherein the following ratios are present:
[0044] (Al2O3+ B2O3) / Σ Modifier>1
[0045] In this ratio, each component is expressed in mol.% and the modifier is an alkali metal oxide. In a specific embodiment, the glass comprises, is substantially composed of, or is composed of: 58-72 mol.% SiO2; 9-17 mol.% Al2O3; 2-12 mol.% B2O3; 8-16 mol.% Na2O; and 0-4 mol.% K2O, wherein the following ratios are used:
[0046] (Al2O3+ B2O3) / Σ Modifier>1
[0047] Another example of a suitable glass composition comprises, substantially comprises, or consists of: 60-70 mol.% SiO2; 6-14 mol.% Al2O3; 0-15 mol.% B2O3; 0-15 mol.% Li2O; 0-20 mol.% Na2O; 0-10 mol.% K2O; 0-8 mol.% MgO; 0-10 mol.% CaO; 0-5 mol.% ZrO2; 0-1 mol.% SnO2; 0-1 mol.% CeO2; less than 50 ppm As2O3; and less than 50 ppm Sb2O3; wherein 12 mol.% ≤ Li2O + Na2O + K2O ≤ 20 mol.% and 0 mol.% ≤ MgO + CaO ≤ 10 mol.%.
[0048] Another example of a suitable glass composition includes alkali metal aluminosilicate glass comprising, substantially comprising, or comprising: 64-68 mol.% SiO2; 12-16 mol.% Na2O; 8-12 mol.% Al2O3; 0-3 mol.% B2O3; 2-5 mol.% K2O; 4-6 mol.% MgO; and 0-5 mol.% CaO, wherein: 66 mol.% ≤ SiO2 + B2O3 + CaO ≤ 69 mol.%; Na2O + K2O + B2O3 + MgO + CaO + SrO > 10 mol.%; 5 mol.% ≤ MgO + CaO + SrO ≤ 8 mol.%; (Na2O + B2O3) ≤ Al2O3 ≤ 2 mol.%; 2 mol.% ≤ Na2O ≤ Al2O3 ≤ 6 mol.%; and 4 mol.% ≤ (Na2O + K2O) ≤ Al2O3 ≤ 10 mol.%. Other examples of the use of this method to generate ion-exchangeable glass structures are described in US Application Publication No. 2014-0087193 A1 and US Patent No. 9,387,651, the entire contents of which are incorporated herein by reference.
[0049] In alternative embodiments, the glass material comprises an alkali metal aluminosilicate glass composition comprising 2 mol% or more of Al2O3 and / or ZrO2, or 4 mol% or more of Al2O3 and / or ZrO2.
[0050] Glass-ceramic materials can be used in conjunction with the ion-exchange glass layers described herein, and can be formed by melting or by other known methods such as rolling, thin rolling, slot drawing, or float glass.
[0051] Available glass-ceramics can be characterized by the methods used to form them. Such glass-ceramics can be formed by float glass processes, melt glass processes, slot drawing processes, thin rolling processes, or combinations thereof. The liquid viscosity of some glass-ceramics often hinders the use of high-volume forming methods (e.g., float glass, slot drawing, or melt drawing). For example, some known glass-ceramics are formed from precursor glasses with a liquidus viscosity of about 10 kP, which is unsuitable for melt drawing, where a liquidus viscosity higher than about 100 kP or even higher than about 200 kP is typically required. Glass-ceramics formed by low-volume forming methods (e.g., thin rolling) can exhibit enhanced opacity, varying degrees of translucency, and / or surface gloss. Glass-ceramics formed by high-volume methods (e.g., float glass, slot drawing, or melt drawing) can achieve very thin layers. Glass-ceramics formed by melt drawing can achieve pristine surface finishes and thinness (e.g., about 2 mm or less). Suitable examples of glass-ceramics may include Li2O-Al2O3-SiO2 system (i.e. LAS-system) glass-ceramics, MgO-Al2O3-SiO2 system (i.e. MAS-system) glass-ceramics, including glass-ceramics of any one or more crystalline phases selected from mullite, spinel, α-quartz, β-quartz solid solution, lepidolite, lithium pyrosilicate, β-spodumene, nepheline and alumina, and combinations thereof.
[0052] The ion-exchange glass layer described herein may have any suitable thickness, such as about 2 mm or less. In some cases, the ion-exchange glass layer described herein has a thickness of about 0.1 mm to about 2 mm (e.g., about 0.1 mm to about 0.5 mm, about 0.1 mm to about 0.3 mm, about 0.1 mm to about 0.25 mm, about 0.3 mm to about 1 mm, about 0.2 mm to about 0.5 mm, or about 0.5 mm to about 2 mm).
[0053] The combination of thicknesses of the ion-exchange glass layer and the negatively doped graphene layer can include, but is not limited to, 0.5 mm / 0.1 nm, 1 mm / 1 nm, 0.5 mm / 0.5 nm, 1 mm / 0.1 nm or 0.1 mm / 0.3 nm.
[0054] The glass articles described herein may further include an encapsulation layer that substantially encapsulates a negatively doped graphene layer. Figure 6 An example of a glass article 600 comprising a negatively doped graphene layer 108, an ion-exchange glass layer 102, and an encapsulation layer 114 is shown. The encapsulation layer 114 can be as follows: Figure 6The first main surface 104 of the ion-exchange glass layer 102 is shown to substantially cover the ion-exchange glass layer 102, or the negatively doped graphene layer 108 may substantially encapsulate the first main surface 104 of the ion-exchange glass layer 102 without substantially covering it (not shown).
[0055] The encapsulation layer can be made of any suitable material, such as Al2O3 deposited by atomic layer deposition methods known in the art. Other suitable materials for the encapsulation layer include, but are not limited to, silicon nitride, aluminum nitride, zirconium nitride, titanium nitride, hafnium nitride, tantalum nitride, silicon oxide, aluminum oxide, or titanium oxide. For example, the encapsulation layer can be made of SiO2, Al2O3, SiON, or SiN. x form.
[0056] This document also considers devices that include the glass articles described herein. The glass articles described herein are scalable to any size for any device ranging from wearable devices to desktop devices, and can be sub-components of larger systems that utilize the properties of glass in some related manner. Examples of devices that may include the glass articles described herein include electronic devices, optical devices, or optoelectronic devices.
[0057] Figure 7 This is a perspective view of an electronic device 120 incorporating the glass articles described herein, and an example of its manufacturing method. Reference Figure 7 Figure (a) shows an ion-exchange glass layer 102, wherein the first main surface 104 and the second main surface 106 (not shown) contain K from the ion-exchange process. + Its thickness (t) can vary between 5 μm and 50 μm. Figure 7 Figure (b) illustrates the process for fabricating the graphene device: (1) initial cleaning of the ion-exchange glass layer 102 using any suitable organic solvent, UV lithography and evaporation of the metal contacts—the first for the Hall bar 116 and the second for increasing the thickness of the first contact 118 and the second contact 118A; (2) transfer of graphene 109 by wet etching and post-annealing. A third lithography patterning of graphene 109 onto the Hall bar region, removal of excess by, for example, reactive ion etching (RIE), and removal of excess by, for example, reactive ion etching (RIE); (3) providing the electronic device 120 by encapsulation with Al2O3 via atomic layer deposition (ALD), wherein graphene 109 is negatively doped at one point by contact with the ion-exchange glass layer to form a negatively doped graphene layer 108. Figure 7A first contact 118 and a second contact 118A are also shown positioned on the ion-exchange glass layer 102, the first contact 118 and the second contact 118A being electrically coupled via a negatively doped graphene layer (not shown). The first contact 118 can be electrically coupled to a first trace 119 and the second contact 118A can be electrically coupled to a second trace 119A, the first trace 119 and the second trace 119A being electrically coupled via a negatively doped graphene layer (not shown), wherein the first contact 118, the first trace 119, the second contact 118A and the second trace 119A are each positioned on the ion-exchange glass layer 102.
[0058] Use, for example Figure 7 The apparatus shown performs electrical measurements to obtain the sheet resistance (R), carrier density (Ns), and electron mobility (μH), respectively. In one embodiment, a measurement of R is first obtained, followed by a Hall measurement to evaluate the levels of carrier density and electron mobility.
[0059] Eight samples were prepared on ion-exchange glass layers of different thicknesses (see example). Figure 8 Each sample contained two Hall strips / sample for statistical analysis. The results are summarized in Table 1. The ion exchange thickness mentioned in Table 1 corresponds to the thickness of the ion exchange layer at the first main surface of the ion exchange glass layer that has been ion-exchanged. However, it should be understood that the thickness of the ion exchange layer at the second main surface of the ion exchange glass layer that has been ion-exchanged is similar to the thickness of the ion exchange layer at the first main surface of the ion exchange glass layer that has been ion-exchanged.
[0060] Table 1
[0061]
[0062] Four months later, the sheet resistance of several devices was measured again, showing an increase of 100-160 Ω / sq, which still indicates a high level of graphene doping over time. Figure 9 The results obtained for samples 1-8 are shown, along with the graphene doping (y-axis) achieved by varying the thickness of the ion-exchange glass layer (x-axis). The results fall within -10... 14 to -3 x 10 14 cm -2 Within a high level of n-doped regions. This is similar to the common doping values of graphene when transferred to a standard substrate such as fused silica (where the doping level is in the range of 10). 12 Compared to other samples within the same range, all samples showed strong n-doping.
[0063] Although this specification may include numerous details, these should not be considered as limitations on its scope, but rather as descriptions of features that may be specific to particular embodiments. Certain features previously described in the context of individual embodiments may also be implemented in combination in a single embodiment. Conversely, several features described in the context of a single embodiment may also be implemented individually or in any suitable sub-combination in multiple embodiments. Furthermore, although features may function in certain combinations as described above, and may even be initially claimed as such, one or more features from the claimed combination may, in some cases, be removed from said combination, and said claimed combination may extend to sub-combinations or variations thereof.
[0064] Similarly, although operations are described in a specific order in the accompanying drawings or diagrams, this should not be construed as requiring such operations to be performed in the specific order shown or sequentially, or requiring the execution of all described operations to achieve the desired result. In some cases, multitasking and parallel processing may be advantageous.
[0065] In the foregoing description, in the several views shown in the accompanying drawings, the same reference numerals denote the same or corresponding parts. It should also be understood that, unless otherwise specified, terms such as “top,” “bottom,” “outward,” and “inward” are convenience terms and should not be construed as restrictive terms. Furthermore, whenever a group is described as comprising at least one of a set of elements and combinations thereof, it should be understood that said group may comprise, consist of, or be composed of any number of the listed elements individually or in combination with each other.
[0066] Similarly, whenever a group is described as consisting of at least one of a set of elements and combinations thereof, it should be understood that the group may consist individually or in combination with each other of any number of the listed elements. Unless otherwise stated, numerical ranges include both the upper and lower limits of the range as recorded. As used herein, unless otherwise stated, the indefinite articles “a” and “an” and the corresponding definite article “the” mean “at least one” or “one or more”.
[0067] As used herein, the term “about” may allow for a degree of variability in a value or range, for example, within 10%, 5%, or 1% of the limits of the value or range.
[0068] As used herein, the term “substantially” means the majority or most, such as at least about 50%, 60%, 70%, 80%, 90%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.9%, 99.99%, or at least about 99.999% or more.
[0069] As used herein, the term “substantially none” means less than about 30%, 25%, 20%, 15%, 10%, 5%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05%, 0.001%, or less than about 0.0005% or less or about 0% or 0%.
[0070] It will be apparent to those skilled in the art that various modifications and variations can be made without departing from the spirit or scope of the illustrated embodiments. Since modifications, combinations, sub-combinations, and variations of the disclosed embodiments that incorporate the spirit and essence of the illustrated embodiments will be apparent to those skilled in the art, the specification should be construed as including all contents within the scope of the appended claims and their equivalents.
[0071] While the disclosure herein relates to certain exemplary implementations, it should be understood that these implementations are presented in an illustrative rather than limiting manner.
[0072] All publications and patents mentioned in the foregoing specification are incorporated herein by reference in their entirety. Various modifications and variations to the use of the described compositions, methods, and techniques will be apparent to those skilled in the art without departing from the scope and spirit of the described techniques. Although the present technology has been described in conjunction with specific exemplary embodiments, it should be understood that the claimed invention should not be unduly limited to such specific embodiments. Indeed, various modifications to the described modes of implementation that will be apparent to those skilled in the art are within the scope of the appended claims.
[0073] The following implementation schemes are provided, and their numbers should not be interpreted as indicating a level of importance:
[0074] Implementation scheme 1 relates to a glass article comprising: an ion-exchange glass layer including a first main surface of the ion-exchange glass layer and a second main surface of the ion-exchange glass layer opposite to the first main surface of the ion-exchange glass layer; and at least one negatively doped graphene layer having a first main surface of the negatively doped graphene layer and a second main surface of the negatively doped graphene layer opposite to the first main surface of the negatively doped graphene layer; the first main surface of the negatively doped graphene layer is positioned opposite at least a portion of at least one of the first main surface and the second main surface of the ion-exchange glass layer, the negatively doped graphene layer having at least about 10 13 cm -2 The carrier density.
[0075] Implementation scheme 2 relates to a glass article as described in implementation scheme 1, wherein the negatively doped graphene layer has about 10 13 cm -2 To about 10 15 cm-2 The carrier density.
[0076] Implementation scheme 3 relates to a glass article as described in implementation schemes 1-2, wherein the negatively doped graphene layer has a sheet resistance of about 200 Ω / sq to about 500 Ω / sq.
[0077] Implementation scheme 4 relates to a glass article as described in implementation schemes 1-3, wherein the negatively doped graphene layer has a thickness of approximately 80 cm. 2 / V·s to approximately 800 cm 2 Electron mobility per V·s.
[0078] Implementation scheme 5 relates to a glass article as described in embodiments 1-4, wherein an intermediate layer is positioned between at least a portion of the first main surface of the negatively doped graphene layer and at least a portion of at least one of the first main surface of the ion-exchange glass layer or the second main surface of the ion-exchange glass layer.
[0079] Implementation scheme 6 relates to a glass article as described in implementation schemes 1-5, wherein at least a portion of at least one of the first main surface of the ion exchange glass layer and the second main surface of the ion exchange glass layer includes the ion exchange depth of the compression layer.
[0080] Implementation scheme 7 relates to a glass article as described in implementation schemes 1-5, wherein at least a portion of the first main surface of the ion-exchange glass layer or the second main surface of the ion-exchange glass layer includes the ion-exchange depth of the compression layer.
[0081] Implementation scheme 8 relates to a glass article as described in implementation schemes 1-7, wherein the first main surface of the negatively doped graphene layer is in direct contact with at least a portion of at least one of the first main surface of the ion-exchange glass layer and the second main surface of the ion-exchange glass layer.
[0082] Implementation scheme 9 relates to glass articles as described in implementation schemes 1-8, wherein the negative doping of the negatively doped graphene layer is induced by an ion-exchange glass layer.
[0083] Implementation scheme 10 relates to a glass article as described in implementation scheme 9, wherein the negative doping of the negatively doped graphene layer is induced by positively charged ions present in the ion-exchange glass layer.
[0084] Implementation scheme 11 relates to a glass article as described in implementation scheme 10, wherein the positively charged ions include alkali metal ions.
[0085] Implementation scheme 12 relates to a glass article as described in implementation scheme 10 or 11, wherein the positively charged ions include potassium ions.
[0086] Implementation scheme 13 relates to a glass article as described in implementation schemes 1-12, wherein the negatively doped graphene layer comprises a single negatively doped graphene layer.
[0087] Implementation scheme 14 relates to a glass article as described in implementation schemes 1-12, wherein the negatively doped graphene layer comprises a graphene stack.
[0088] Embodiment 15 relates to a glass article as described in Embodiments 1-14, wherein the negatively doped graphene layer has a thickness of about 0.1 nm to about 1 nm.
[0089] Embodiment 16 relates to a glass article as described in Embodiments 1-15, wherein the ion-exchange glass layer has a thickness of about 0.1 nm to about 2 nm.
[0090] Embodiment 17 relates to a glass article as described in Embodiments 1-16, wherein the ion-exchange glass layer is an ion-exchange alkali metal aluminosilicate glass composition or an ion-exchange alkali metal aluminoborosilicate glass composition.
[0091] Implementation scheme 18 relates to a glass article as described in embodiments 1-17, further comprising an encapsulation layer that substantially encapsulates the negatively doped graphene layer.
[0092] Implementation scheme 19 relates to a glass article as described in implementation scheme 18, wherein the encapsulation layer comprises silicon nitride, aluminum nitride, zirconium nitride, titanium nitride, hafnium nitride, tantalum nitride, silicon oxide, aluminum oxide, or titanium oxide.
[0093] Implementation scheme 20 relates to an apparatus comprising glass articles as described in implementation schemes 1-19.
[0094] Implementation scheme 21 relates to an apparatus as described in implementation scheme 20, wherein the apparatus is an electronic device, an optical device or an optoelectronic device.
[0095] Implementation scheme 22 relates to an apparatus as described in implementation schemes 20-21, further comprising a first contact and a second contact positioned on an ion-exchange glass layer, the first contact and the second contact being electrically coupled via the negatively doped graphene layer.
[0096] Implementation scheme 23 relates to an apparatus as described in embodiments 20-22, further comprising a first contact electrically coupled to a first trace and a second contact electrically coupled to a second trace, the first trace and the second trace being electrically coupled via the negatively doped graphene layer, wherein the first contact, the first trace, the second contact and the second trace are each positioned on the ion-exchange glass layer.
[0097] Embodiment 24 relates to a method for preparing a glass article as described in Embodiments 1-19, comprising: obtaining or providing an ion-exchange glass layer comprising a first main surface and a second main surface of an ion-exchange glass layer; and positioning a graphene layer on at least a portion of the first main surface of the ion-exchange glass layer to produce at least one negatively doped graphene layer.
[0098] Implementation scheme 25 relates to the method as described in implementation scheme 24, wherein the negatively doped graphene layer has about 10 13 cm -2 To about 10 15 cm -2 The carrier density.
[0099] Implementation scheme 26 relates to the method as described in implementation schemes 24-25, wherein the negatively doped graphene layer has a sheet resistance of about 200 Ω / sq to about 500 Ω / sq.
[0100] Implementation scheme 27 relates to the method as described in embodiments 24-26, wherein the negatively doped graphene layer has a thickness of approximately 80 cm. 2 / V·s to approximately 800 cm 2 Electron mobility per V·s.
[0101] Implementation scheme 28 relates to the method as described in implementation schemes 24-27, further comprising positioning an intermediate layer between at least a portion of the first main surface of the negatively doped graphene layer and at least a portion of at least one of the first main surface of the ion-exchange glass layer and the second main surface of the ion-exchange glass layer.
[0102] Implementation scheme 29 relates to the method as described in implementation schemes 24-28, wherein at least a portion of at least one of the first main surface of the ion exchange glass layer and the second main surface of the ion exchange glass layer includes the ion exchange depth of the compression layer.
[0103] Implementation scheme 30 relates to the method as described in implementation schemes 24-29, wherein at least a portion of the first main surface of the ion exchange glass layer or the second main surface of the ion exchange glass layer includes the ion exchange depth of the compression layer.
[0104] Implementation scheme 31 relates to the method as described in implementation schemes 24-30, wherein the first main surface of the negatively doped graphene layer is in direct contact with at least a portion of at least one of the first main surface of the ion-exchange glass layer and the second main surface of the ion-exchange glass layer.
[0105] Implementation scheme 32 relates to the method as described in implementation schemes 24-31, wherein the negative doping of the negatively doped graphene layer is induced by the ion-exchange glass layer.
[0106] Implementation scheme 33 relates to the method as described in implementation schemes 24-32, wherein positively charged ions present in the ion-exchange glass layer induce negative doping of the negatively doped graphene layer.
[0107] Implementation scheme 34 relates to the method as described in implementation scheme 33, wherein the positively charged ions include alkali metal ions.
[0108] Implementation scheme 35 relates to the method as described in implementation schemes 24-34, wherein the positively charged ions include potassium ions.
[0109] Implementation scheme 36 relates to the method as described in implementation schemes 24-35, wherein the negatively doped graphene layer comprises a single negatively doped graphene layer.
[0110] Implementation scheme 37 relates to the method as described in implementation schemes 24-35, wherein the negatively doped graphene layer comprises a graphene stack.
[0111] Implementation scheme 38 relates to the method as described in implementation schemes 24-37, wherein the negatively doped graphene layer has a thickness of about 0.1 nm to about 1 nm.
[0112] Implementation scheme 39 relates to the method as described in implementation schemes 24-38, wherein the ion exchange glass layer has a thickness of about 0.1 mm to about 2 mm.
[0113] Embodiment 40 relates to the method as described in Embodiments 24-39, wherein the ion exchange glass and the ion exchange glass layer are ion exchange alkali metal aluminosilicate glass compositions or ion exchange alkali metal aluminoborosilicate glass compositions.
[0114] Implementation scheme 41 relates to the method as described in implementation schemes 24-40, further comprising positioning an encapsulation layer that substantially encapsulates the negatively doped graphene layer.
[0115] Implementation scheme 42 relates to the method as described in implementation scheme 41, wherein the encapsulation layer comprises silicon nitride, aluminum nitride, zirconium nitride, titanium nitride, hafnium nitride, tantalum nitride, silicon oxide, aluminum oxide, or titanium oxide.
Claims
1. A glass article comprising: An ion-exchange glass layer, comprising a first main surface of the ion-exchange glass layer and a second main surface of the ion-exchange glass layer opposite to the first main surface of the ion-exchange glass layer; A negatively doped graphene layer having a first main surface of the negatively doped graphene layer and a second main surface of the negatively doped graphene layer opposite to the first main surface of the negatively doped graphene layer; as well as The first primary surface of the negatively doped graphene layer is positioned opposite at least a portion of at least one of the first primary surface of the ion-exchange glass layer or the second primary surface of the ion-exchange glass layer. The negatively doped graphene layer has 10 13 cm -2 Up to 10 15 cm -2 The carrier density.
2. The glass article of claim 1, wherein the negatively doped graphene layer has a sheet resistance of 200 Ω / sq to 500 Ω / sq.
3. The glass article according to any one of claims 1-2, wherein the negatively doped graphene layer has an 80 cm² depth. 2 / V·s to 800 cm 2 Electron mobility per V·s.
4. The glass article according to any one of claims 1-2, wherein the intermediate layer is positioned between at least a portion of the first main surface of the negatively doped graphene layer and at least a portion of at least one of the first main surface of the ion-exchange glass layer or the second main surface of the ion-exchange glass layer.
5. The glass article according to any one of claims 1-2, wherein the first main surface of the negatively doped graphene layer is in direct contact with at least a portion of at least one of the first main surface of the ion-exchange glass layer or the second main surface of the ion-exchange glass layer.
6. The glass article according to any one of claims 1-2, wherein the negative doping of the negatively doped graphene layer is induced by positively charged ions present in the ion-exchange glass layer.
7. The glass article according to any one of claims 1-2, wherein the negatively doped graphene layer has a thickness of 0.1 nm to 1 nm.
8. The glass article according to any one of claims 1-2, further comprising an encapsulation layer encapsulating the negatively doped graphene layer.
9. The glass article of claim 8, wherein the encapsulation layer comprises silicon nitride, aluminum nitride, zirconium nitride, titanium nitride, hafnium nitride, tantalum nitride, silicon oxide, aluminum oxide, or titanium oxide.
10. An apparatus comprising a glass article as claimed in any one of claims 1-9, further comprising a first contact electrically coupled to a first trace and a second contact electrically coupled to a second trace, the first trace and the second trace being electrically coupled via the negatively doped graphene layer, wherein the first contact, the first trace, the second contact and the second trace are each positioned on the ion-exchange glass layer.
11. The apparatus of claim 10, wherein the apparatus is an electronic device, an optical device, or an optoelectronic device.
12. A method for manufacturing glass articles, comprising: Obtain or provide an ion-exchange glass layer comprising a first main surface and a second main surface of an ion-exchange glass layer; as well as The graphene layer is positioned on at least a portion of the first main surface of the ion-exchange glass layer to produce a negatively doped graphene layer. The negatively doped graphene layer has 10 13 cm -2 Up to 10 15 cm -2 The carrier density.
13. The method of claim 12, wherein the negatively doped graphene layer has a sheet resistance of 200 Ω / sq to 500 Ω / sq.
14. The method of claim 12, wherein the negatively doped graphene layer has an 80 cm² depth. 2 / V·s to 800 cm 2 Electron mobility per V·s.
15. The method of claim 12, further comprising positioning an intermediate layer between at least a portion of the first main surface of the negatively doped graphene layer and at least a portion of the first main surface of the ion-exchange glass layer.
16. The method of claim 12, wherein at least a portion of the first main surface of the negatively doped graphene layer is in direct contact with the first main surface of the ion-exchange glass layer.
17. The method of claim 12, wherein positively charged ions present in the ion-exchange glass layer induce negative doping of the negatively doped graphene layer.
18. The method of claim 12, wherein the negatively doped graphene layer has a thickness of 0.1 nm to 1 nm.
19. The method of claim 12, further comprising positioning an encapsulation layer for encapsulating the negatively doped graphene layer.
Citation Information
Patent Citations
Methods for producing ion exchanged glass and resulting apparatus
US20140087193A1
Methods for producing ion exchanged glass and resulting apparatus
US9387651B2
Electronic device including graphene-based layer(s), and / or method of making the same
CN102656702A
Method of preparing three-dimensional graphene glass composite
CN107298533A